The Extent of The Contribution of Ethical Leadership in Enhancing Human Talent Management practices : an Analytical of The Some of the Teachers at the Sulaimaniyah Polytechnic University - Fatah Amin, Shaima; Mohammed Hassan, Chia (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
This study aims to determine the extent of the contribution of ethical leadership in enhancing human talent management practices among faculty members. This study follows a descriptive correlative approach where the study population consisted of all faculty members with different age and educational background at the Technical University in Sulaymaniyah in 2021-2022. The sample size was 119 from a total population of 535 faculty members. The result shows that there is a significant and positive correlation between ethical leadership and human talent management. Moreover, there is a significant effect for each dimension of moral leadership represented by the orientation towards individuals, justice, power-sharing, role clarification, and integrity in the human talent management variable. The result also shows that the absence of significant differences in each of the ethical leadership variables and human talent management could be the source of the personal characteristics of the responding individuals.